Body mass index and variability in meal duration and association with rate of eating - Simon, Stacey L.; Pan, Zhaoxing; Marden, Tyson; Zhou, Wenru; Ghosh, Tonmoy; Hossain, Delwar; Thomas, J. Graham; McCrory, Megan A.; Sazonov, Edward; Higgins, Janine (Frontiers in Nutrition, 2022)
Background: A fast rate of eating is associated with risk for obesity but existing studies are limited by reliance on self-report and consistency of eating rate has not been examined across all meals in a day. The goal of the current analysis was to examine associations between meal duration, rate of eating, and body mass index (BMI) and to assess variance of meal duration and eating rate across different meals during the day. Methods: Using an observational cross-sectional study design, Nonnon-smoking participants aged 18-45 years (N=29) consumed all meals (breakfast, lunch, and dinner) on a single day in a pseudo free living environment. Participants were allowed to choose any food and beverages from a university food court and consume their desired amount with no time restrictions. Weighed food records and a log of meal start and end times, to calculate duration, were obtained by a trained research assistant. Spearman correlations and multiple linear regressions examined associations between BMI and meal duration and rate of eating. Results: Participants (N=29) were 65% male and 48% White. Shorter meal duration was associated with higher BMI at breakfast but not lunch or dinner, after adjusting for age and sex (p = 0.03). Faster rate of eating was associated with higher BMI across all meals (p = 0.04) and higher energy intake for all meals (p < 0.001). Intra-individual rate of eating was not significantly different across breakfast, lunch and dinner (p = 0.96). Conclusion: Shorter breakfast and faster rate of eating across all meals were associated with higher BMI in a pseudo free-living environment. An individual’s rate of rate eating is constant over all meals in a day. These data support weight reduction interventions focusing on rate of eating at all meals throughout the day and provide evidence for specifically directing attention to breakfast eating behaviors.